Post delivery obstetric hemorrhage. - Bárbara Lucía Cabezas Poblet; María Antonia Cabezas Poblet; Evangelina Dávila Cabo de Villa; Rolando T. Espín González; María Herrera Pírez; Zoraida Montero Padrón (Medisur)
-